Evaluation of a bifactor model and psychometric properties of FACES III in Peruvian students - Aaron Caycho Caja; César Abraham Castilla Arias (Interacciones)
Background: To analyze the internal structure of the Family Adaptability and Cohesion Evaluation Scales-FACES III by evaluating three tentative models. Method: Non-probability sampling of 306 Peruvian students of both sexes between 15 and 26 years of age. The structural properties and internal consistency of the Original, Bifactorial and One-dimensional models were studied in detail. Results: The bifactorial model has a better fit than the remaining models, but was discarded as it does not satisfy the criteria of the suggested evaluation indices. Likewise, difficulties are observed in the internal consistency of the Flexibility subscale except for the One-Dimensional Model. Conclusion: FACES III is an instrument with consistency and internal structure problems directly associated with the presence of the Flexibility subscale as reported in previous studies.